Pemanfaatan Limbah Beton Pada Campuran Hot Rolled Sheet Base Ditinjau Dari Aspek Propertis Marshall - Rahman, Zakaria Ade; , Senja Rum Harnaeni, S.T., M.T (2016)
Problems of environmental damage caused by the exploitation stone mining for building materials, be advocates for reusing waste materials from building demolition such as waste concrete be a mixture on the road pavement. Therefore, the aim of this study is to determine how much potential waste concrete when used as a partial replacement of coarse aggregate in the mixture of HRS-Base gap gradation by viewed from the aspects of Marshall Properties. This study used an experimental method based on hot mix asphalt design guidelines that are reviewed by Marshall method, according to SNI 06-2489-1990 and General Specification of Bina Marga 2010 Revision III. Begins by examining the characteristics of the materials used are asphalt, fresh aggregate and waste concrete. Followed by drafting a combined grading as aggregate composition of the mixture. After that, make Marshall Specimen for testing Phase I by using fresh aggregate as a standard material in order to determine the Optimum Bitumen Content (KAO) on the variation of bitumen content of 5.5%; 6.0%; 6.5%; 7.0%; 8.0% wich evaluated from the eligible value of Marshall Properties. Based on the KAO, then make Marshall Specimen for testing Phase II using waste concrete as a partial replacement of fresh coarse aggregate with a variety of replacement 0%; 20%; 40%; 60%; 80% to get the value of Marshall Properties. The results showed, waste concrete can be used as a partial replacement of coarse aggregate in the mixture of HRS-Base gap gradation. Amplified by viewed from Marshall Properties at KAO 6.3%. The value of Marshall Stability, Flow, and VMA, from the five levels of waste concrete meets the specifications required by Bina Marga 2010 Revision III. The greater the level of concrete waste, Marshall Stability tends to go down, Flow and VMA tends to rise. While the value of VFWA, VIM, and Marshall Quotient, only partially meets the specifications. In the VFWA value tends to fall to reach the minimum specifications at waste concrete level of 30%, and MQ down to reach the minimum specified limit at a level of 54% of waste concrete. The VIM value tends to go up and touch the maximum limit specification at a level of 20% of waste concrete. Based on the eligible value of Marshall Properties, acquired Optimum levels of waste by 10%. However, up to the level of 20% of waste concrete can still produce a mixture that meets General Specification of Bina Marga 2010 Revision III.